University and students readiness for big data analytics / Sarah Yusoff, Rohana Yusof and Nur Hidayah Md Noh - Yusoff, Sarah; Yusof, Rohana; Md Noh, Nur Hidayah (2020)
Intellipaat.com which provides professional online training courses has listed jobs in big data and data science as the highest paying job in 2019. Malaysia expects to face a shortage of 7,000 to 15,000 data science professionals in 2019. To meet this demand university should be able to produce graduates that are ready to grab job opportunities in this field. But the question is,” Are our graduates ready for big data analytics?” This is the question this research tries to answer. The research objective is to identify the significant criteria that could be used to determine student readiness to take up job opportunities in the field of big data analytics. The questionnaire for this research was developed using Survey Monkey application and distributed online to all students who enrolled in various degree programs and Masters program in Data Science, Faculty of Computer and Mathematical Sciences. 151 students had answered the questionnaire. Data analyzed using Smart PLS showed that the significant variables that indicate student readiness for a career in big data anlytics are attitude, data communication skills and teamwork. Results from this research are expected to input information on student readiness for job opportunities as data scientists and identify activities and facilities needed to be upgraded to prepare students for big data analytics.